Evolution Characteristics of a High-Level Asymmetric Fracture-Seepage Community and Precise Coalbed Methane Drainage Technology during Mining of Outburst-Prone Coal Seam Groups - Hongbing Wang; Zhiheng Cheng; Tie Li; Liang Chen; Quanle Zou; Shengli Yang; Jialin Cao (Shock and Vibration)
The aim of this study is to explore the coupling relationship between fractures in overlying strata and gas seepage fields for pressure relief during mining of outburst-prone coal seam groups and to quantitatively characterize the distribution characteristics of favorable areas for coalbed methane (CBM) drainage in mining-induced fractures of overlying strata. For these purposes, by taking Shaqu No. 1 Coal Mine (Lvliang City, Shanxi Province, China) as a research object, this research studied migration and caving characteristics of overlying strata by combining physical similar material simulation, numerical simulation, and field measurement. Moreover, this study analyzed spatial distribution patterns of mining-induced fractures in overlaying strata, quantitatively characterized distribution parameters of asymmetric-oblique-quadrilateral fracture development zones in overlying strata, and precisely divided areas favorable for CBM drainage. On this basis, evolution laws of an asymmetric fracture-seepage community in overlying strata in outburst-prone coal seam groups were obtained, thus optimizing design parameters for directional drilling in the fracture zone in overlying strata. The research results demonstrate that, due to mining-induced influences, strata present different migration and rupture patterns along rupture lines on both sides. Because of different rupture angles α and β, mining-induced fractures in overlying strata are distributed as an asymmetric-oblique-quadrilateral fracture development body in space. Furthermore, based on the coupling relationship between fracture development states and pressure-relief gas seepage in the fracture development zone in overlying strata of the 4305 rear working face in the mine, this research obtained rupture angles α ∈ [74, 90) and ß ∈ (70, 82] on both sides of the fracture development zone. Moreover, the intervals favorable for CBM drainage for pressure relief on both sides of the fracture development zone in overlying strata of 4305 rear working face in the mine were separately determined as xaj ≤ 22.68 m and 24 m ≤ xβj ≤ 37.8 m. If the gas drainage system is designed in this zone, it is of great significance to precise and efficient pressure-relief CBM drainage in the fracture zone and ensure production safety in the mining space.